(untitled) (Eurasian Scientific Herald, 2022)
This article is devoted to the topic of rational food consumption and its role in the body system of preschoolers. The article reveals the following questions: "What is the system of proper nutrition in kindergarten"; "What is meant by proper nutrition and what it should be for preschoolers"; "What to pay attention to when catering preschool children"; "What products are preferred when catering". The forms of work with parents are formulated, recommendations on the nutrition of children are given